Mechanisms of Auditory Verbal Hallucination in Schizophrenia - Cho, Raymond; Wu, Wayne (Frontiers in Psychiatry, 2013)
Recent work on the mechanisms underlying auditory verbal hallucination (AVH) has been heavily informed by self-monitoring accounts that postulate defects in an internal monitoring mechanism as the basis of AVH. A more neglected alternative is an account focusing on defects in auditory processing, namely a spontaneous activation account of auditory activity underlying AVH. Science is often aided by putting theories in competition. Accordingly, a discussion that systematically contrasts the two models of AVH can generate sharper questions that will lead to new avenues of investigation. In this paper, we provide such a theoretical discussion of the two models, drawing strong contrasts between them. We identify a set of challenges for the self-monitoring account and argue that the spontaneous activation account has much in favor of it and should be the default account. Our theoretical overview leads to new questions and issues regarding the explanation of AVH as a subjective phenomenon and its neural basis. Accordingly, we suggest a set of experimental strategies to dissect the underlying mechanisms of AVH in light of the two competing models.